INTERNALISASI NILAI-NILAI BUDAYA RELIGIUS PESANTREN DALAM MEMBENTUK KARAKTER SANTRI PUTRI - Farah Putri Aprilia; Miftahul Huda; Mochamad Fadlani Salam; Muhtadin; Mukhlishah (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2024)
Pesantren is an educational institution and social unit where students go to study. The goal of Islamic boarding schools is to produce a generation with noble morals and piety. Through character education, female students are shaped into individuals with noble morals, and Islamic boarding schools serve as a place for cultivating religious character among their students. This research aims to determine the extent to which Islamic boarding school religious and cultural values are internalized in shaping the character of female students. The method used in this research is descriptive analysis with a qualitative approach. The research results reveal that internalization has a significant impact in improving religious character, as demonstrated by an increase in: 1). Sincerity, 2). Simplicity, 3). Ukhuwwah Islamiyyah (Islamic brotherhood), and 4). Freedom